A daily diary study of internalised weight bias and its psychological, eating and exercise correlates. Issue 3 (4th March 2019) - Carels, Robert A.; Hlavka, Reid; Selensky, Jennifer C.; Solar, Chelsey; Rossi, James; Caroline Miller, J.
Abstract: Objective: The current investigation extends ecological momentary assessment (EMA) and daily diary weight stigma research in internalised weight bias (IWB). This investigation used daily diaries to examine the relationship between IWB, mood, coping, body appreciation, exercise behaviours and eating behaviours.Design: The study sample consisted of individuals who were overweight or obese (85% female) with MBMI = 36.0, SDBMI = 6.2. Participants completed a daily diary each evening and wore a Fitbit for 30 days.Main Outcome Measures: Participants reported on IWB, mood, coping, body appreciation, exercise behaviours and eating behaviours. Results: Both within- and between-subjects IWB were significantly related to positive affect, negative affect, several coping responses, body appreciation, eating behaviours and the urge to avoid exercise. Exploratory analyses indicated that positive and negative affect mediated many of the associations between IWB and coping responses, body appreciation, and eating and exercise behaviours. Conclusion: This investigation provides evidence that IWB experiences have daily impacts on psychological well-being, body appreciation, coping, eating and exercise behaviours. Also, this study raises awareness about IWB and its potential impact on psychological well-being and health behaviours.